Hand hygiene compliance in Greek nursing personnel - Malliarou, Maria; Karathanasi, Konstantinia; Andreanidis, Elias; Kotrotsiou, Evagelia; Sarafis, Pavlos (My University, 2013)
To investigate the compliance of hand hygiene of Greek nurses.
Keywords: Hand hygiene; Greek nurses